2021
DOI: 10.3390/plants10061125
|View full text |Cite
|
Sign up to set email alerts
|

Quality Attributes and Storage of Tomato Fruits as Affected by an Eco-Friendly, Essential Oil-Based Product

Abstract: The preservation of fresh produce quality is a major aim in the food industry since consumers demand safe and of high nutritional value products. In recent decades there has been a turn towards the use of eco-friendly, natural products (i.e., essential oils-EOs) in an attempt to reduce chemical-based sanitizing agents (i.e., chlorine and chlorine-based agents). The aim of this study was to evaluate the efficacy of an eco-friendly product (EP—based on rosemary and eucalyptus essential oils) and two different ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 50 publications
0
24
1
Order By: Relevance
“…An important study published in this Special Issue, conducted by Xylia et al [ 6 ], evaluated the efficacy of an eco-friendly product based on rosemary and eucalyptus Eos and two different application methods (vapor and dipping) on the quality attributes of tomato fruits, and the obtained results indicated that eco-friendly products based on the studied EOs were able to maintain the quality of tomato fruits. In addition, Chrysargyris et al [ 7 ] studied the vapor application of sage EO for maintaining tomato fruit, where the quality attributes were more affected in green fruits and were less affected red fruits.…”
Section: Antimicrobial Phytotoxic Activity and Agri-food Applicationsmentioning
confidence: 99%
“…An important study published in this Special Issue, conducted by Xylia et al [ 6 ], evaluated the efficacy of an eco-friendly product based on rosemary and eucalyptus Eos and two different application methods (vapor and dipping) on the quality attributes of tomato fruits, and the obtained results indicated that eco-friendly products based on the studied EOs were able to maintain the quality of tomato fruits. In addition, Chrysargyris et al [ 7 ] studied the vapor application of sage EO for maintaining tomato fruit, where the quality attributes were more affected in green fruits and were less affected red fruits.…”
Section: Antimicrobial Phytotoxic Activity and Agri-food Applicationsmentioning
confidence: 99%
“…These changes can be delayed through the application of eugenol (Tables 1 and 2) and are associated with lower ethylene production and a notable delay in the production of peak ethylene (Figure 1). The effects on ethylene production of applying essential oils to fruits is well established, and it was previously found that the application of rosemary and eucalyptus essential oil reduced ethylene production in tomato [28]. In table grapes [15], treatments with different essential oils, including eugenol, were associated with reduced ethylene production.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to the camphor content, the highest values for the 1.8-cineole content were obtained in the pre-flowering stage (22.61%). When compared the 1.8-cineole content with the earlier studies, diverse results were found, such as 6.19%-10.52% (Gürbüz et al, 2017), 41.25%-45.96% (Yıldırım, 2018), 37.50% (Khanjani et al, 2021), 10.81% (Xylia et al, 2021), 17.79%-23.40% (Micić et al, 2021), 26.40%-49.10% (Flamini et al, 2021), 40.10% (Christopoulou et al, 2021, 30.89%-31.61% (Dzięcioł, 2021), 28.97%-32.18% (Elyemni et al, 2022), 32.50%-51.79% (Rathore et al, 2022), 30.26% (Mwithiga et al, 2022), 25.26%-29.15% (Yeddes et al, 2022), 11.86% (Karakaş and Bekler, 2022).…”
Section: Chemical Composition Of Essential Oilmentioning
confidence: 90%
“…The highest values for the isoborneol content were obtained in the mid-and post-flowering stage. Isoborneol content in the previous studies was found different, such as 3.48 % (Martínez et al, 2009), 0.20% (Hussain et al, 2010), 5.68% (Asressu and Tesema, 2014), 2.28%-9.8% (Farhat et al, 2017), 6.04%-12.02% (Gürbüz et al, 2017), 8.10% (Caputo et al, 2018), 11.96%-14.89% (Yıldırım, 2018), 0.11% (Micić et al, 2021), 6.00% (Khanjani et al, 2021), 30.29% (Xylia et al, 2021).…”
Section: Chemical Composition Of Essential Oilmentioning
confidence: 90%